The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1093/schbul/sby014.065
|View full text |Cite
|
Sign up to set email alerts
|

17.1 a Randomized Controlled Trial of Cannabidiol in Schizophrenia

Abstract: BackgroundBoth preclinical and human research suggest that cannabidiol (CBD) has antipsychotic properties. This study assessed the safety and effectiveness of CBD in patients with schizophrenia.MethodsPatients with schizophrenia (n=88) were randomized to receive CBD (1000 mg/day) or placebo alongside their existing antipsychotic medication for 6 weeks. Participants were assessed before and after treatment using the PANSS, BACS, GAF scales, and the CGI Improvement and Severity scales.ResultsCompared those given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…In the second, more recent randomised controlled trial (n = 36), there was no difference in patient scores for symptoms of schizophrenia or cognitive function for those receiving 600 mg/day of CBD for 6 weeks, compared with placebo (Boggs et al 2018b). In contrast, in the third study, patients (n = 88) given a higher dose (1000 mg/ day) of CBD for a 6-week period exhibited improved scores for psychotic symptoms, relative to the placebo group, and were more likely to be rated by physicians as showing an overall improvement in their condition and having a decreased severity of illness (McGuire et al 2018). Although inconsistent, the results from these early phase trials indicate that CBD may be useful as an adjunctive therapy in the treatment of schizophrenia.…”
Section: Schizophreniamentioning
confidence: 88%
See 3 more Smart Citations
“…In the second, more recent randomised controlled trial (n = 36), there was no difference in patient scores for symptoms of schizophrenia or cognitive function for those receiving 600 mg/day of CBD for 6 weeks, compared with placebo (Boggs et al 2018b). In contrast, in the third study, patients (n = 88) given a higher dose (1000 mg/ day) of CBD for a 6-week period exhibited improved scores for psychotic symptoms, relative to the placebo group, and were more likely to be rated by physicians as showing an overall improvement in their condition and having a decreased severity of illness (McGuire et al 2018). Although inconsistent, the results from these early phase trials indicate that CBD may be useful as an adjunctive therapy in the treatment of schizophrenia.…”
Section: Schizophreniamentioning
confidence: 88%
“…; McGuire et al . ). In the first study (randomised, double‐blinded), patients ( n = 39) received 200 mg/day of CBD or an active control (amisulpride, an antipsychotic medication) once a day for an initial 1‐week period, after which the doses of CBD were increased in individuals (if tolerated) up to four times per day (800 mg/day), followed by maintenance of the attained dosage for a further 3 weeks (Leweke et al .…”
Section: Evidence For Cbd Health Benefitsmentioning
confidence: 97%
See 2 more Smart Citations
“…The selective CB1 receptor antagonist, rimonabant (approved in the EU for weight loss) failed to show improvements in global cognitive function in [Boggs et al, ]. However, a study of an oily solution containing cannabidiol—GWP42003 as adjunctive therapy for schizophrenia reported that 500 mg bid for 5 weeks reduced positive symptoms of psychosis in patients stabilized on antipsychotic therapy [McGuire et al, ]. Additional Phase II studies using cannabinoids are recruiting patients with acute psychosis.…”
Section: Pipeline Drugs For Schizophrenia In Recently Completed Clinimentioning
confidence: 99%